Social context alters host behavior and infection risk. (18th April 2018) - Keiser, Carl N; Rudolf, Volker H W; Sartain, Elizabeth; Every, Emma R; Saltz, Julia B
Abstract : Disease risk is influenced by hosts' traits and their social environment. We tested how variation in host behavior and group sex ratio alter transmission of a fungal pathogen in Drosophila melanogaster . Hosts varied in behaviors that influence pathogen transmission, though factors of social context were the only predictors of infection risk: more infections were observed in female-biased groups. Social context may therefore be a more powerful predictor of disease risk compared to individual traits. Abstract: Variation in infection risk and transmission potential are widespread in human and wildlife diseases and play a central role in host–pathogen dynamics. To explain this variation, most studies focus on linking host traits to differences in pathogen exposure, infection, and transmission, but typically do not account for hosts' social context. Yet, an individual's risk of acquiring infection is likely influenced jointly by their own traits and their social environment. Here, we use 3 natural genotypes of the fruit fly Drosophila melanogaster to test how variation in pathogen transmission is linked to differences in host behavior and social context. We constructed groups of 12 flies from 1 of 3 different genotypes and 5 different sex ratios (0%, 33%, 50%, 67%, or 100% female) in a fully factorial design. To each group, we added a male or female "primary case" fly that had been exposed to the generalist fungal entomopathogen Metarhizium robertsii . We then recorded groups' aggregation behavior, mating frequency, and infection prevalence. Aggregation and mating behavior were influenced either jointly or additively by fly genotype and sex ratio. However, a combination of individual-level (mating history; the sex of the primary case) and group-level factors (sex ratio) jointly influenced individuals' infection risk. There were more infections in female-biased groups, though the sex of the primary case also influenced sex-biased mortality and the relationship between individuals' mating history and infection risk. Thus, an individual's social environment can be an important predictor of social dynamics and their survival outcomes.